CD133(+) Liver Cancer Stem Cells from Methionine Adenosyl Transferase 1A–Deficient Mice Demonstrate Resistance to Transforming Growth Factor (TGF)-β–Induced Apoptosis - Ding, Wei (2009)
Methionine adenosyltransferase (MAT) is an essential enzyme required for S-adenosylmethionine biosynthesis. Hepatic MAT activity falls during chronic liver injury, and mice lacking Mat1a develop spontaneous hepatocellular carcinoma by 18 months. We have previously demonstrated that CD133(+)CD45(−) oval cells isolated from 16-month-old Mat1a(−/−) mice represent a liver cancer stem cell population. The transforming growth factor β (TGF-β) pathway constitutes a central signaling network in proliferation, apoptosis, and tumorigenesis. In this study, we tested the response of tumorigenic liver stem cells to TGF-β. CD133(+)CD45(−) oval cells were isolated from premalignant 16-month-old Mat1a(−/−) mice by flow cytometry and expanded as five clone lines derived from a single cell. All clone lines demonstrated expression of both hepatocyte and cholangiocyte markers and maintained a small population (0.5% to 2%) of CD133(+) cells in vitro, and three of five clone lines produced tumors. Although TGF-β1 inhibited cell growth equally in CD133(−) and CD133(+) cells from each clone line, the CD133(+) population demonstrated significant resistance to TGF-β–induced apoptosis compared with CD133(+) cells. Furthermore, CD133(+) cells demonstrated a substantial increase in mitogen-activated protein kinase (MAPK) pathway activation, as demonstrated by phosphorylated extra-cellular signal-regulated kinase levels before and after TGF-β stimulation. MAPK inhibition using mitogen-activated protein kinase kinase 1 (MEK1) inhibitor PD98059 led to a significant increase in TGF-β–induced apoptosis in CD133(+) cells. Conversely, a constitutively active form of MEK1 blocked the apoptotic effects of TGF-β in CD133(−) cells. CONCLUSION: CD133(+) liver cancer stem cells exhibit relative resistance to TGF-β–induced apoptosis. One mechanism of resistance to TGF-β–induced apoptosis in CD133(+) cancer stem cells is an activated mitogen-activated protein kinase/extracellular signal-regulated kinase pathway.